PEDAGOGICAL MONITORING OF TEACHING PROFICIENCY IN PROFESSIONAL EDUCATION - Lukashenko, Dmitry; Sergeeva, Marina; Kirillova, Tatyana; Oreshkina, Anna; Solncev, Sergeevich (Revista Inclusiones, 2020)
The educational system of the Russian Federation is an object of large-scale reform, covering all existing levels, from nursery and primary schools to educational institutions of higher education. The paradigm shift affected not only the content of curricula, methods and forms of training, but also the approach to the professional development of teachers. All changes taking place in Russian schools and universities at present are due to the social and economic changes that determine the optimization of organizational structures, the transformation of the essence of pedagogical culture, and the increase in requirements for assessing the competence of a teacher. A highly professional teacher should provide humanistic education, meet basic social and moral needs, taking into account the intellectual, psychological, ethnic and other diversity of the youth. Moreover, for pedagogical science and practice, ambiguous changes occurring in various directions are characteristic.